Social Work Education's Effect on Retention. - Wermeling, Linda; Hunn, Vanessa; McLendon, Tara (Journal of Social Work Education)
This study explores the relationship between social work education and a propensity of social workers to leave the profession. A convenience sample was drawn from alumni lists in the mid-South of the United States, with 785 participants completing a Web-based survey. This survey included items specific to demographic information and level of satisfaction with academic rigor of social work education. Results indicate that social workers who left, or intended to leave the profession, rated the quality of their social work education significantly lower than those who remained in the profession. In addition, those who remained in the profession held a significantly greater number of licenses than those who left. Implications and recommendations for social work education, practice, and research are discussed.